2007
DOI: 10.1210/jc.2007-0267
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian Hormone Levels in Peripubertal Daughters of Women with Polycystic Ovary Syndrome

Abstract: AMH concentrations are increased in peripubertal PCOSd. These findings, along with the results of our previous study, suggest that PCOSd appear to show an increased follicular mass that is established during early development, and persists during puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
67
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 30 publications
5
67
1
4
Order By: Relevance
“…In our subjects, AMH was not correlated with basal insulin or HOMA-IR levels in group 1, group 2 or group 3. We believe this supports that 5 should also be studied.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our subjects, AMH was not correlated with basal insulin or HOMA-IR levels in group 1, group 2 or group 3. We believe this supports that 5 should also be studied.…”
Section: Discussionsupporting
confidence: 73%
“…Women with PCOS were shown to have higher AMH levels compared to healthy women. Different studies have also reported higher AMH levels in prepubertal and peripubertal daughters of women with PCOS [4][5][6] . These reports suggest that changes in AMH production associated with PCOS may be observed even during the prepubertal period.…”
mentioning
confidence: 96%
“…The sensitivity of newer ELISAs has improved (0.006 ng/ml) and a more recent study has reported appreciable levels of AMH in the serum of infants and young girls (Sir-Petermann et al 2006). However, these same investigators measured higher levels in peripubertal girls (Crisosto et al 2007), which suggest that serum AMH is relatively low in females before puberty. Thus, lower serum AMH concentration in 10-week-old SD hamsters may simply reflect their prepubertal state, but still, the underlying etiology remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated androgen levels in women with PCOS are the cause of high levels of AMH [43]. Another study notes that the AMH levels of the prepubertal daughters of women with PCOS were higher than those in in the prepubertal daughters of women without PCOS [44]. This indicates that these children have a high risk of becoming PCOS in the future.…”
Section: Discussionmentioning
confidence: 99%